2021
DOI: 10.1177/23094990211034004
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and intraoperative factors contributing to patient satisfaction after bi-cruciate stabilized total knee arthroplasty

Abstract: Background: One of the causes of dissatisfaction following total knee arthroplasty (TKA) is abnormal knee kinematics. A newly designed bi-cruciate stabilized (BCS) TKA system has been developed to produce close-to-normal kinematics because of its anatomic tibiofemoral articular geometry and cam-post mechanism. Although BCS TKA is expected to improve patient satisfaction, no reports have described the appropriate technique or soft tissue handling required to achieve excellent satisfaction with BCS TKA. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Patients in SG were given preoperative health preaching and individualized assessment by anesthesiologists, which is beneficial to alleviate their anxiety and improve the perioperative cooperation. Patients with hypertension and diabetes must receive blood pressure and glucose control before operation, and can drink some water to improve circulation stability and reduce postoperative insulin resistance, thus accelerating the recovery of gastrointestinal function [ 20 ]. Ishii Yoshinori et al showed that insulin resistance could be reduced if patients undergoing TKR were to eat and drink water moderately before surgery, and their hospital stay could be shortened to (8.54 ± 0.54) d [ 21 ], which was consistent with the results obtained herein.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in SG were given preoperative health preaching and individualized assessment by anesthesiologists, which is beneficial to alleviate their anxiety and improve the perioperative cooperation. Patients with hypertension and diabetes must receive blood pressure and glucose control before operation, and can drink some water to improve circulation stability and reduce postoperative insulin resistance, thus accelerating the recovery of gastrointestinal function [ 20 ]. Ishii Yoshinori et al showed that insulin resistance could be reduced if patients undergoing TKR were to eat and drink water moderately before surgery, and their hospital stay could be shortened to (8.54 ± 0.54) d [ 21 ], which was consistent with the results obtained herein.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports regarding intraoperative kinematics during TKA [ 6 , 7 , 8 , 9 , 11 , 12 , 14 , 15 , 17 , 20 , 21 , 22 , 24 , 25 , 28 , 30 , 35 ] using a navigation system. Kinoshita et al [ 15 ] reported that the normal rotational kinematics of the knee can be restored by controlling soft‐tissue balance during surgery and that medial rotational stability is important for the ROM responsible for inducing the ideal rotational movement.…”
Section: Discussionmentioning
confidence: 99%
“…23 The intraoperative predictor of patients’ satisfaction after bi-cruciate stabilized TKA was medial joint stability at 90°. 24 A modified gap balance technique was used in an attempt to achieve the same gap at 0° and 90°, but midflexion laxity could not be adjusted during surgery. In a previous study, joint gap kinematics were measured using a tensor device, and the center size of the joint gap was tight in extension and deep flexion and loose at midflexion ranges, especially at 30° of flexion.…”
Section: Discussionmentioning
confidence: 99%